(untitled) (Bangladesh Agronomy Journal, 2023)
An experiment was conducted in the month of November, 2021 at Crop Physiology and Ecology Laboratory, Hajee Mohammad Danesh Science and Technology University, Dinajpur, Bangladesh to study the impact of tobacco industry wastewater on germination and early seedling traits of five mung bean accessions (BD-10022, BD-10023, BD-10024, BD-10026 and BD-10027) following factorial completely randomized design (CRD) with three replications. Mung bean accession, tobacco industry wastewater and their interaction significantly interacted on germination and seedling traits of mung bean. Tobacco industry wastewater reduced the germination percentage, germination rate and co-efficient of germination but insisted longer shoot and root as well as escalated the seedling dry weight of mung bean as compared to tap water. Among the five mung bean accessions, BD-10024 and BD-10027 performed comparatively better performance regarding germination and seedling traits, respectively under wastewater conditions. Bangladesh Agron. J. 2022, 25(2): 129-137